The effectiveness of the similarity strategy in developing creative thinking among students of the Department of Art Education in the subject of handicrafts (Journal of the College of Basic Education, 2022)
The current study aimed to identify the effectiveness of the similarities strategy in developing creative thinking among students of the Department of Art Education in the subject of handicrafts. As for the third chapter, the research procedures in which the researcher followed the experimental method for two groups (experimental - control), and the research community consisted of students from the Department of Art Education - College of Basic Education - Al-Mustansiriya University - the first stage, numbering (210) students, and to achieve the goal of the research, the researcher Determining the subject of handicrafts and building an achievement test according to it to measure and achieve the students of the two research groups (experimental and control), which was characterized by honesty and stability, and the adoption of the test scale of creative thinking (Saeed Khairallah, 1981) modified to measure the development of creative thinking.The researcher used the statistical package (Spss) as it is the most appropriate for his current study, as it was found that the experimental group students and the development of their creative thinking who studied according to the similarities strategy were superior to the control group who studied in the traditional way.